Expansion and presence of free radio in Chiapas, a phenomenon of globalization - Martínez Mendoza, Sarelly (2015)
In Chiapas, border state in the south of Mexico, in 2002 began to emerge free radios, also known as illegal or “pirates”. In 2014, work 130 of these radio stations, mostly religious (68), followed by commercial (41), community radio (11), zapatista radio (5), municipal radio (3) and partisan radio (2). The objective of this work was to identify these radio stations, describing their programmatic bar and forms of operation. Through interviews and monitoring programming, mainly, was able to understand the complex network of free radio communication, which operates in this border state, which has the greatest number of stations of this type in Mexico. Although 130 free radios were located, growing dynamics that have registered, suggests that they will continue to multiply and that it is urgent to know them, to establish mechanisms for dialogue and negotiation with the authorities. In Chiapas, the radio free covers with their emissions almost the entirety of the state territory, in some places, such as San Cristobal de Las Casas, we are experiencing a saturation in the quadrant, while in other regions, particularly La Sierra, the free radio is alone.